Acute myocardial infarction in a young woman with ulcerative colitis: A case report and literature review. Issue 47 (November 2017) - Zhang, Yong; Hao, Xuezeng; Zheng, Xiangying; Zhao, Huaibing; Zhang, Wei; Zhang, Lijing
Abstract: Rationale: Myocardial infarction due to nonatherosclerotic coronary thrombosis in young woman with ulcerative colitis is rare. Patient concerns: A 23-year-old Chinese woman with a 3-year history of ulcerative colitis was admitted to the coronary care unit due to prolonged chest pain. Diagnoses: Myocardial infarction due to nonatherosclerotic coronary thrombosis was diagnosed in this young woman. Lessons: Coronary artery thrombosis in ulcerative colitis is a serious condition and can occur in the young population.